STRATEGI INDONESIA DALAM MENGHADAPI LARANGAN EKSPOR KELAPA SAWIT RED II OLEH UNI EROPA TAHUN 2018 - Yolla Ersafitri; Pazli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes Indonesia's strategy in dealing with the ban on palm oil exports by the European Union. The impact of the dispute makes Indonesian oil palm farmers lose money and affects the national economy which can be said to depend on this commodity. Indonesia then fought for rights in the palm oil trade in the international sphere with the help of the WTO as a mediator. This study uses a qualitative method using existing reading materials as a source of exposure about Indonesian palm oil exports and European Union policies, with data collection techniques through literature studies and document analysis from several books, journals and websites. This study uses the perspective of Liberalism and Policy Theory. This research shows that Indonesia has implemented various measures to increase its palm oil production and exports in the face of European Union policies. Such as holding the 6th Ministerial Meeting CPOPC strongly protested the Renewable Energy Directive II (RED II) Policy and the Delegated Act. Indonesia also carries out promotional activities regarding palm oil and the use of Indonesian Sustainable Palm Oil (ISPO) certificates. Indonesia made a Statement with numbers G/TBT/W/565 to the WTO Technical Barriers to Trade Committee which aims to ask for clarification on several matters concerning the EU's RED II. The WTO processed this case by offering a dispute resolution resolution that reduced the obstacles encountered in the palm oil trade. This means that Indonesia won the lawsuit and inevitably the European Union must obey it so that their image in the international community does not become bad. Keywords: Strategy, RED II, Palm Oil, WTO, European Union